Plays : Fifth Series - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"Plays: Fifth Series" by John Galsworthy is a collection of plays written during the early 20th century. This series encompasses various themes, with a notable focus on familial dynamics, societal expectations, and personal conflicts. The plays center around characters such as John Builder, a businessman and aspiring mayor, and his daughters, Athene and Maud, who grapple with their identities and choices in a rapidly changing society. At the start of "A Family Man," the first play in the series, we are introduced to John Builder and his wife, Julia, as they discuss their family, particularly their estranged daughter, Athene. John expresses a desire to reconcile with Athene, who has distanced herself due to ideological differences, especially regarding her pursuit of artistic freedom and independence. As tension rises, it becomes evident that John's vision of familial duty conflicts with the aspirations of his daughters, setting the stage for an exploration of generational conflicts and the evolving roles of women in society. This opening portion lays the groundwork for dramatic confrontations that illuminate the characters' struggles with authority, autonomy, and the definition of family life. (This is an automatically generated summary.)
A family man -- Loyalties -- Windows.
Release date is 2004-09-26
Produced by David Widger
Keywords: England -- Drama